PENGARUH PROMOSI KESEHATAN TERHADAP KESADARAN MASYARAKAT DALAM PENCEGAHAN COVID-19 DI PUSKESMAS CITRA MEDIKA KOTA LUBUK LINGGAU - Nana Indra Lesmana; Veby Fransisca Rozi; Susi Eryani (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2022)
Background : The low level of public awareness to carry out social distance can be seen by the many individuals who are active outside the home by gathering without wearing a mask or maintaining a safe distance only for recreational purposes, grouping each other, thus allowing the spread is still a big task. The problem in this study is the low level of public awareness in preventing Covid-19 in the Citra Medika Health Center, Lubuk Linggau City. The purpose of this study was to determine the effect of health promotion on public awareness in preventing covid-19 in the Citra Medika Health Center, Lubuk Linggau City. Methods : The design of this study used a pre experimental design using a pre and post test design. The population in this study amounted to 630 people. The number of sample members is 10 to 20 respectively, so the sample to be studied is 20 people using a purposive sampling technique. The data used are primary data and secondary data. The analysis used is univariate analysis and bivariate analysis, the statistical test used is the T test. Results : The results of the univariate analysis showed that the average value of public awareness in preventing covid-19 before and carrying out health promotion was 20.2 and 40.4. The results of the bivariate analysis showed that the p-value was 0.000. Conclusion : That there was an effect of health promotion on public awareness in preventing covid-19 in the Citra Medika Health Center, Lubuk Linggau City. It is hoped from the results of this study that the puskesmas and health workers can prepare interesting promotional media and provide health promotion with different methods that are more effective, as attractive as possible to increase public awareness in preventing covid-19.